MANFAAT HASIL BELAJAR MEMPERBAIKI POLA DASAR BADAN BAWAH UNTUK TUBUH DENGAN PROBLEMA KHUSUS SEBAGAI KESIAPAN MENJADI PATTERN MAKER - Umi Yasmin, - (2018)
Penelitian ini mengkaji tentang manfaat hasil belajar memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus sebagai kesiapan menjadi pattern maker. Pentingnya peran pattern maker untuk membuat pola busana dapat memanfaatkan hasil belajar memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus. Tujuan dari penelitian ini adalah untuk memperoleh data mengenai manfaat hasil belajar memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus sebagai kesiapan menjadi pattern maker ditinjau dari pengetahuan, pemahaman materi memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus, teknik mengukur badan bawah untuk tubuh dengan problema khusus sertaanalisis pola dasar dan cara memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus sebagai kesiapan menjadi pattern maker. Metode yang digunakan pada penelitian ini yaitu metode deskriptif dengan alat pengumpul data berupa angket. Sampel penelitian ini menggunakan sampel total, dengan mengambil dari populasi mahasiswa Program Studi Pendidikan Tata Busana Departemen PKK FPTK UPI angkatan 2015 yang telah mempelajari materimemperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus pada mata kuliah analisis pola busana dengan jumlah 48 orang. Hasil penelitian ini menunjukkan bahwa materi pembelajaran memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus dapat membekali mahasiswa untuk siap menjadi pattern maker. Simpulan hasil penelitian bahwa sebagian besar mahasiswa merasakan adanya manfaat hasil belajar memperbaiki pola dasar badan bawah untuk tubuh dengan problema khusus sebagai kesiapan menjadi pattern maker.----- This study review the benefits of learning outcomes to improve the basic body pattern for the body with special problems as a readiness to be a pattern maker. The body shape of each woman is different because it has many indentations and bulges so it can be a problem if the shape and location is not ideal. The importance of the role of pattern maker to overcome the problem that is must be able to analyze the existing problems so as to improve the basic pattern of clothing in accordance with the body shape. The purpose of this study is to obtain data on the benefits of learning outcomes to improve the basic body pattern for the body with a special problem as a readiness to be a pattern maker in terms of knowledge, understanding of the basic body fix the basic body for the body with special problems, body weight measuring technique for the body with special problems as well as archetypal analysis and how to improve the underlying body pattern for the body with special problems as a readiness to be a pattern maker. The method used is descriptive method with data collection tool in the form of questionnaire. The sample of this study using the total sample, taking from the student population Education Studies Program Department of PKK FPTK UPI force 2015 who have studied the material improves the basic body pattern down to the body with special problems in the course of fashion patterns analysis with the number 48 people. The results of this study indicate that most of the respondents (91.67%) understand that the measured person should not use useful footwear to obtain the right size, (87.50%) of respondents know the shape of the enlarged diamond diamond in the middle part and shrink at the bottom is useful in analyzing skirt pattern, and (83,33%) of respondent express measure of hip circumference at back pattern, then minimize pelvis and crotchet to thigh circle in pattern of pantalon then fix the pattern is useful to improve pants pattern pattern with problem there are lines and folds. Conclusion of the research result that most students feel the benefit of learning result to improve basic body pattern for body with special problem as readiness to become pattern maker.